Predation by brown trout (Salmo trutta) along a diversifying prey community gradient - Jensen, Hallvard; Kahilainen, Kimmo K.; Amundsen, Per-Arne; Gjelland, Karl øystein; Tuomaala, Anti; Malinen, Tommy; Bøhn, Thomas (Canadian Journal of Fisheries and Aquatic Sciences, 2008)
Predation has a fundamental role in aquatic ecosystems, but the relative importance of factors governing prey selection by predators remains controversial. In this study, we contrast five lakes of a subarctic watershed to explore how prey community characteristics affect prey selection and growth rate of the common top predator, brown trout ( Salmo trutta ). The lakes constitute a distinct gradient of different coregonid prey fish, ranging from monomorphic common whitefish ( Coregonus lavaretus ) to polymorphic whitefish co-occurring with vendace ( Coregonus albula ). The brown trout was a morph–species- and size-specific pelagic predator, selecting the small-sized, pelagic whitefish morph or vendace over the benthic whitefish morphs. In all lakes, the average prey size increased with predator size, but small-sized prey were also included in the diet of large predators. The selection of small-sized, pelagic prey fish appeared to be a favourable foraging strategy for the brown trout, yielding higher growth rates and an earlier ontogenetic shift to piscivory. The findings emphasize that piscivory appear to be shaped by the diversity, size-structure, and abundance of available prey in a given community.